An empirical research on the Non-Linear effect of financial asset allocation on the development of main business. (September 2020) - Ren, Keke
Abstract: With respect to the hot issue of "breaking away from entity economy, and transforming to virtual economy" in Chinese economy over the years, an empirical test is carried out in the paper considering the influence of financial asset allocation on the development of main business in entity enterprises by regarding A-share entity enterprises in Henan Province from 2009 to 2018 as the research samples. According to the research, entity enterprises in Henan Province are of huge differences in financial asset allocation and in general, the configuration level is not high, and the main business is facing lower operating incomes. From the perspective of different industries, financial asset allocation of enterprises in the manufacturing industry presents U-shaped relations with the development of main business, and when the level of financial asset allocation in enterprises reaches to 10.47%, incomes obtained by financial asset allocation can promote the development of main business, but the above effect isn't obvious in other industries. The research conclusion made in the paper is that entity enterprises can benefit more by making reasonable investment decisions, improving the utilization rate of idle funds, perfecting the effectiveness of financial market, and depositing into financial institutions, and these effects can provide the major basis to realize "the mutual promotion of finance and industry".